Comparison of Seismic Performance of Shear Wall and Bracing Systems in Residential Flats in Silangkitang Village North Tapanuli - Abiyyu, Muhammad Fauzan; Hasibuan , Samsul Abdul Rahman Sidik (LPPM Universitas Andalas, 2025)
Indonesia lies within the Pacific Ring of Fire at the convergence of three major tectonic plates, making earthquake-resistant design a critical challenge for multi-story buildings. Structural systems such as reinforced concrete shear walls and steel bracing are commonly employed to enhance lateral load resistance. This study evaluates and compares the seismic performance of shear wall and bracing systems in a three-story residential flat located in Silangkitang Village, North Tapanuli, using nonlinear static (pushover) analysis conducted in ETABS v18. The analysis results indicate that, in the X-direction, the shear wall structure achieves a total displacement of 66.84 mm with a base shear of 8512.78 kN, whereas the braced structure exhibits a total displacement of 119.19 mm with a base shear of 9773.20 kN. In the Y-direction, the shear wall structure records a total displacement of 166 mm and a base shear of 13,228.69 kN, while the braced structure achieves 173 mm and 8210.53 kN, respectively. These findings demonstrate that, although both systems satisfy the same structural performance level criteria, the shear wall system provides superior lateral stiffness and more favorable displacement characteristics compared to the bracing system.